Cover Feature: Cystobactamid 507: Concise Synthesis, Mode of Action, and Optimization toward More Potent Antibiotics (Chem. Eur. J. 32/2020). Issue 32 (8th May 2020) - Elgaher, Walid A. M.; Hamed, Mostafa M.; Baumann, Sascha; Herrmann, Jennifer; Siebenbürger, Lorenz; Krull, Jana; Cirnski, Katarina; Kirschning, Andreas; Brönstrup, Mark; Müller, Rolf; Hartmann, Rolf W.
Abstract : Optimization of the natural antibiotic cystobactamid 507 targeting DNA gyrase and topoisomerase IV was attained by structure– and conformation—activity relationship studies. The bioactive conformation was recognized as syn using conformationally locked analogues via intramolecular hydrogen bonds. The new compounds displayed improved target inhibition, antibacterial activity, stability to metabolism and the resistance factor AlbD. Mode of action study revealed that cystobactamids bind to the DNA part of the gyrase–DNA complex at the minor groove with no intercalation. More information can be found in the Full Paper by R. W. Hartmann et al. on page 7219 .